Creativity, Inc. - Catmull, Edwin E. (London : Bantam Press, 2014)
As a young man, Ed Catmull had a dream: to make the world's first computer-animated movie. He nurtured that dream first as a Ph.D. student at the University of Utah, where many computer science pioneers got their start, and then forged an early partnership with George Lucas that led, indirectly, to his founding Pixar with Steve Jobs and John Lasseter in 1986. Nine years later and against all odds, 'Toy Story' was released, changing animation forever. Since then, Pixar has dominated the world of animation, producing such beloved films as 'Monsters, Inc.', 'Finding Nemo', 'The Incredibles', 'Up', and 'WALL-E', which have gone on to set box-office records and garner 27 Academy Awards. Now, in this book, Catmull reveals the ideals and techniques, honed over years, that have made Pixar so widely admired-and so profitable.
Keywords: Creative ability in business; Corporate culture; Organizational effectiveness; Business and Management